Loving and Healing a Hurt City: Planning a Green Monterrey Metropolitan Area - Rob Roggema; Igor Ishi Rubio Cisneros; Rodrigo Junco López; Paulina Ramirez Leal; Marina Ramirez Suarez; Miguel Ortiz Díaz (Land)
In many conurbations, the pressure on the quality of living increases and affects the most vulnerable human and non-human populations the most. This article describes a proposal for the mapping and design investigation of how a green metropolis can be developed. The approach distinguishes between the landscape producing pain, the ways of healing, and the opportunities to create environments that people can love. This approach reveals concrete and widespread pain in the metropolis, such as impacts on natural landscapes (rivers and mountains), air pollution, ecological degradation, and hydrological disconnections. The strategy to remediate this pain is to uncover hidden and altered creeks and rivers, creating an abundant zone of ecological space around them before human activities and urbanization change the land uses. In addition to this, specific design principles have been developed for hydro-ecological corridors, water retention, green islands, and greenways. Designs for these places can be replicated to support a healing strategy in the Monterrey Metropolitan Area (MMA). Each place creates an environment that the urban residents will appreciate and preserve. The approach to analyzing landscape pain, designing healing strategies, and promoting local places of love can be applied to enhance the quality of life for many urban residents and non-human ecologies in metropolitan areas around the globe.